THE USE OF POSSE (PREDICT, ORGANIZE, SEARCH, SUMMARIZE, AND EVALUATE) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT AT THE TENTH GRADE OF SMK PGRI 2 DENPASAR IN THE ACADEMIC YEAR 2019/2020 - Vety Isma Ulfa; Indah Triana Juliari, I Gusti Ayu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2020)
Abstract This research aims to improve the tenth grade students’ reading comprehension by using POSSE strategy in SMK PGRI 2 Denpasar. It was an action research study which consisted of two cycles.The subjects of the research were students of X grade AK2 of SMK PGRI 2 Denpasar in the academic year 2019/2020. The qualitative data were collected by anlyzing the results of observation and interviewed the students on the learning process. The procedure of the research consisted of some stages, namely: planning, action, observation, and reflection. The instruments used of this research were observation sheet, interview guide, and tests. The method of collecting data were used interview, documentation, observation and test. The results of this research showed that the use of POSSE strategy was succesfully improve the students’ reading comprehension. Based on the quantitative data, the students’ mean scores for the reading comprehension improved from 55 in pre-test to 69 in post test 1 and 79 in post test 2. Meanwhile, from interviewed the students about the use of POSSE strategy showed that it helped the students to understand narrative text and helped them enrich their vocabulary knowledge. Besides that, the use of POSSE strategy could attract their attention in teaching and learning process. Keywords: Reading Comprehension, Narrative Text, POSSE strategy. Abstrak Tujuan dari penelitian ini adalah untuk meningkatkan pemahaman membaca siswa kelas sepuluh dengan menggunakan strategi POSSE di SMK PGRI 2 Denpasar. Penelitian ini adalah penelitian tindakan kelas yang terdiri dari 2 skilus. Subjek penelitian ini adalah terdiri dari 35 siswa kelas X AK2 di SMK PGRI 2 Denpasar tahun ajaran 2019/2020. Data kualitatif dikumpulkan melalui menganalisis hasil observasi dan interview siswa terhadap proses pembelajaran. Prosedur penelitian terdiri dari beberapa tahapan yaitu perencanaan, tindakan, observasi dan refleksi. Instrument dari penelitian ini menggunakan lembar observasi, pedoman wawancara, dan tes. Pengumpulan data menggunakan metode wawancara, dokumentasi, observasi, dan tes evaluasi. Hasil penelitian ini menunjukkan bahwa penggunaan strategi POSSE berhasil untuk meningkatkan pemahaman membaca siswa. Berdasarkan data kuantitatif, nilai rata-rata siswa untuk pemahaman membaca meningkat dari 55 di pre-test, menja1di 69 di post-test 1, dan 79 di post-test 2. Sementara itu, hasil wawancara para siswa tentang penggunaan strategi POSSE menunjukkan bahwa dapat membantu siswa untuk memahami teks naratif dan membantu mereka memperbanyak pengetahuan kosa kata. Selain itu, penggunaan strategi POSSE dapat menarik perhatian mereka dalam proses belajar mengajar. Kata Kunci: Pemahaman membaca, teks naratif, strategi POSSE.